ANALISIS EFISIENSI DAN EFEKTIVITAS RETRIBUSI PASAR TAMAN PASAR BURUNG DAN IKAN HIAS DEPOK DI SURAKARTA - -, Yulita (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
This study aims to determine the performance of one of the government agencies in terms of efficiency and effectiveness of revenue, market acceptance of, and useful to find a picture of developments in the Bird Market Levy Office Park Management and Ornamental Fish Market Depok Surakarta that can later be used to determine the development of revenue, market coming year. This study is a quantitative study with data collection techniques such as interviews, observation, and literature study. Analysis of data using analysis of efficiency, effectiveness, growth rate, and a linear trend. The results of this study indicate that the implementation of collection and revenue, market on Bird Market Park Management Office and Ornamental Fish Depok Surakarta in fiscal year 2011 to fiscal year 2013 was very good in terms of its effectiveness can be seen from the increasing revenue, results of which can exceed the targets set, but less in terms of efficiency, but the trend gained always been progressing increase each year of forecasting future. Keywords: efficiency, effectiveness, growth rate, linear trend